Les Kapsiki: race taurine de l'extreme-Nord camerounais. I. Introduction et barymetrie - Dineur, B.; Thys, E. (1986)
Presents the Kapsiki, a residual Bos taurus breed of far North Cameroon. Data on the environmental and social background, biometrical and phaneroptic evaluations included. A barymetric formula was calculated and a body weight-chest girth conversion table deduced for practical use in the field.